Evaluation of a breastmilk hand expression toolkit: the M.I.L.K survey study - Alibhai, Kameela M.; Murphy, Malia S. Q.; Dunn, Sandra; Keely, Erin; O’Meara, Paloma; Anderson, Josdalyne; El-Chaâr, Darine (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Breastmilk hand expression (BMHE) is recommended to promote lactation, relieve breast engorgement, and collect milk for future infant feedings. Resources to teach this skill are limited and infrequently developed in partnership with the obstetrical population. In collaboration with maternity care experts and individuals with recent breastfeeding experience, we designed a one-page toolkit that describes the process of BMHE and includes step-by-step instructions and images to illustrate the technique. This study aimed to evaluate the readability, clarity of content, layout, and informational value of this BMHE toolkit. Methods Individuals who intended to breastfeed, were currently breastfeeding, or had recently breastfed were electronically surveyed and completed a two-part survey that consisted of radio, multi-select, Likert scale, and open-ended questions. Part one captured sociodemographic factors, obstetrical history, and breastfeeding practices. Part two collected feedback on the BMHE toolkit. Participants were recruited electronically through social media and posters were circulated in antenatal and postnatal care settings in Ottawa, Canada between November 2020 and February 2021. Results Of the 123 participants, 117 (95.1%) had heard of hand expression prior to reviewing the toolkit and 99 (80.5%) had hand expressed before. Among the 48 participants who were no longer exclusively breastfeeding at the time of the survey, 22 (45.8%) had exclusively breastfed their infant for at least six months and 7 (14.6%) had discontinued exclusive breastfeeding within the first month. When asked about the BMHE toolkit, 118 (95.9%) participants said it was informative, 115 (93.5%) said it was easy to understand, and 114 (92.7%) said it was well laid-out. When asked about information seeking behaviours, participants indicated a preference for online resources (58.5%) and video resources (22.0%). Conclusions The BMHE toolkit was well received by participants and the feedback was favourable overall. The survey feedback will be used to create a revised version of the toolkit that has been validated by the obstetrical patient population. Future research should focus on identifying implementation strategies to optimize the use of the toolkit and increase its effectiveness as an educational resource to teach participants correctly BMHE.